Train Service Plan Design under the Condition of Multimodal Rail Transit Systems Integration and Interconnection - Li Lin; Xuelei Meng; Xiaoqing Cheng; Yangyang Ma; Shichao Xu (Journal of Advanced Transportation)
Multimodal rail transit systems integration and interconnection can solve frequent transfer problems and better adapt to disequilibrium passenger flow and space. It is an inevitable choice in the development of various rail transit systems. Firstly, this paper proposes a novel train service plan design model in the scenario of multimodal rail transit systems integration and interconnection. Our model takes into account the costs of both passengers and enterprises, and passengers travel time is converted into cost using passengers’ nonworking time value coefficient. The model contains some conventional constraints such as passenger flow, station capacity, and line carrying capacity. It also considers whether the transportation capacity of different lines is matched, that is, the constraint of capacity matching degree. Secondly, an improved harmonic search algorithm (IHSA) is designed to solve the problem, and a numerical experiment is used to prove the performance of the proposed method. Our research result shows that the model and algorithm proposed in this paper is effective, which can help overcome the drawbacks of the existing independent operation mode of different rail transit systems. This study is also applicable to the scenario of other kinds of rail transit systems integration and interconnection.